Home enteral nutrition recipients: patient perspectives on training, complications and satisfaction - O'SULLIVAN, MARIA; Boland, Karen; Maher, Niamh; O'Hanlon, Carmel; Rice, Niamh; Smyth, Martina; Reynolds, John V. (My University, 2017)
The equitable provision of home enteral nutrition (HEN) in the community can have a transformative effect on patient experience and family life for adults and children alike. While optimising quality of life in HEN patients can be challenging, the initiation of HEN positively impacts this measure of healthcare provision.1 Quality of life scores have been shown to improve in the weeks after hospital discharge, and HEN is physically well tolerated. However, it may be associated with psychological distress, and sometimes reluctance among HEN patients to leave their homes.2 Globally, HEN can attenuate cumulative projected patient care costs through a reduction in hospital admission and complications including hospital acquired infections.3 In an era where the cost of disease related malnutrition and associated prolonged hospital stay is being tackled in our healthcare systems, the role of HEN is set to expand. This is a treatment which has clear clinical and social benefits, and may restore some independence to patients and their families. Rather than the indications for HEN being focused on specific diagnoses, the provision of months of quality life at home for patients is adequate justification for its prescription.4 Previously, a review of HEN service provision in 39 cases demonstrated that patients want structured follow-up after hospital discharge, and in particular, would like one point of contact for HEN education and discharge.5 Management structures, funding challenges and the need for further education, particularly within the primary care setting may limit optimal use of HEN. The Irish Society for Clinical Nutrition and Metabolism (IrSPEN) aims to develop a national guideline document, drawing on international best practice, forming a template and standards for local policy development in the area of HEN service provision, training and follow-up. The first step in guideline development was to investigate patient experience for adults and children alike. Care needs and supports may differ in these distinct populations. The unmet needs of carers of older adults on HEN have been documented,6 although multidisciplinary interventions and evolution of standards for successful discharge will benefit all affected patients and their families. The aim of this study, therefore, was to survey domiciliary HEN clients, to document and analyse user experience, attitudes and complications associated with HEN.
Keywords: Home enteral nutrition; Training; Quality of life; Nutrition